2017
DOI: 10.1590/1981-22562017020.160155
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers, sarcopenia and its diagnostic criteria among the elderly: a systematic review

Abstract: Objective: To identify the relationship between inflammatory markers and sarcopenia, and the diagnostic criteria of the condition among the elderly. Methods: A systematic review was performed based on the consultation of the PubMed and LILACS databases. Eligible original articles were those involving individuals aged 60 years or more, which investigated sarcopenia [low muscle mass (MM) associated with poor muscle strength and/or reduced physical performance, according to the European Working Group on Sarcope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…TNF-α, IL-6, CRP, albumin, WBC count and ESR were found to be associated with low physical performance, muscle strength or muscle mass in older people [8, 9, 13, 14, 16], but other studies failed to find this association [10, 11, 13, 17]. To date, TNF-α, IL-6, albumin and CRP have shown a relation with the development of low muscle strength or muscle mass over time [8, 1315], however, the current body of evidence fails to reveal a marker of chronic inflammation that is univocally associated with measures of sarcopenia in older people [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α, IL-6, CRP, albumin, WBC count and ESR were found to be associated with low physical performance, muscle strength or muscle mass in older people [8, 9, 13, 14, 16], but other studies failed to find this association [10, 11, 13, 17]. To date, TNF-α, IL-6, albumin and CRP have shown a relation with the development of low muscle strength or muscle mass over time [8, 1315], however, the current body of evidence fails to reveal a marker of chronic inflammation that is univocally associated with measures of sarcopenia in older people [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…In its systematic review study, Marguti et al stated that follistatin was only weakly correlated with the physical performance of the elderly. 16 The subgroup analysis of the sarcopenia and normal groups showed a significant negative relationship between waist circumference and follistatin levels. The greater the waist circumference, the lower the follistatin level in the elderly group who did not experience sarcopenia.…”
Section: Discussionmentioning
confidence: 94%
“…The results of this study are consistent with the results of a systematic review study by Marguti KM et al in 2017, which found that follistatin (and 4 other biomarkers) was not associated with sarcopenia. 16 The study by Choi K et al in 2020 also found that follistatin levels were not associated with the incidence of sarcopenia in patients with hepatocellular carcinoma (HCC). 17 Different results were obtained ultimately leading to hypertrophy and muscle growth.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is an imbalance between fat mass and muscle mass that results in an inflammatory process due to changes in anabolic and catabolic mediators. With the reduction of concentrations of anabolic hormones such as testosterone, growth hormone (GH), insulin and IGF-1, catabolism is observed, which prevents muscle synthesis 30 .…”
Section: Discussionmentioning
confidence: 99%